Strategi Penataan Permukiman Kumuh Pesisir Kota Kupang (Suatu Pendekatan Perilaku Lingkungan) - Fanggidae, Linda Welmintje (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2025)
Slums are a common problem in developing cities, such as Kupang City in Eastern Indonesia. The phenomenon of slum development in Kupang City can also be found in coastal areas. As a city with a waterfront city concept, handling of existing conditions must be done immediately to prevent them from expanding and getting worse. If left unchecked, these coastal slums will be able to damage the overall spatial appearance of the city as a waterfront city, considering the importance of coastal areas. There are 78.67 hectares of slum areas in Kupang City, of which approximately 10 hectares are located in coastal areas. The reorganization of coastal slum areas has been undertaken through various strategies to address existing slum problems. The government has implemented physical intervention strategies, in the form of: repairing and constructing environmental infrastructure, as well as livable houses. However, non-physical intervention strategies are still needed in order to maintain the impact of sustainable physical interventions. The implementation of this strategy aims to encourage the formation of environmental behaviors that are expected to foster a new culture, such as a healthy, clean, aesthetic, and sustainable environmental management system, as an important and permanent aspect of people's daily lives.